2014
DOI: 10.1097/01.won.0000436669.79024.b0
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Comparison of a Silicone Tape and a Paper Tape for Gentleness in Healthy Children

Abstract: Gentleness assessments favored the silicone tape compared to a paper tape and warrant further clinical investigation in the neonatal intensive care unit.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(51 citation statements)
references
References 26 publications
0
51
0
Order By: Relevance
“…They evaluated the patient's skin for erythema, edema by a score of 0–4, and skin denudation by a score of 0–4 as described in the following part (adopted from other studies for skin injury [18, 22, 28]). For standardization, both nurse clinicians were briefed about assessment for skin injuries and given pictorial examples of the different severities of injury prior to start of the study.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…They evaluated the patient's skin for erythema, edema by a score of 0–4, and skin denudation by a score of 0–4 as described in the following part (adopted from other studies for skin injury [18, 22, 28]). For standardization, both nurse clinicians were briefed about assessment for skin injuries and given pictorial examples of the different severities of injury prior to start of the study.…”
Section: Methodsmentioning
confidence: 99%
“…Studies comparing the silicone tape to other adhesives in healthy volunteers also used less than 30 patients per group [18, 22]. …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Certain medications, such as long-term use of oral or topical corticosteroids, can also weaken skin and the blood vessels within the skin and make it more vulnerable to tape-induced trauma. 11,12 Dressings made with silicone adhesives also have a low reaction rate (0/45) among individuals at high risk of skin sensitization 13 and induce significantly less pain and discomfort at removal than similar products with traditional acrylic adhesives. 3 Much has been published about the use of adhesive tapes to induce skin trauma for the purpose of dermatological research, 8,9 but little evidence is found regarding estimates of the actual incidence of tape-induced trauma in clinical situations, and particularly among patients with fragile or at-risk skin.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, silicone-based adhesives have been introduced which have significantly lower peel adhesion resulting in a much lower incidence of skin trauma on removal. [5] We may thus conclude that acrylate-based medical tapes and dressing should be used cautiously with a proper tape removal technique in peri- and post-menopausal patients.…”
mentioning
confidence: 99%